Creative Economy to Increase Community Revenue Based on Tourism Object, Medalsari Village, Pangkalan District Karawang Regency - Rismayadi, Budi; Maemunah, Mumun (Journal of Accounting, Business and Finance Research, 2018)
The important role of counselling and training activities for the community on improving community skills that can be used to improve the quality of life and welfare by utilizing the resources and potential in the villages is the goal to be achieved. Through counselling and training activities, community get information and insight, so people can understand deeply about the creative economy and its benefits. The material of the counselling delivered is adjusted to the potential of resources in the village. Counselling materials include the understanding of what is the meant of creative economy including creative industry and its definition, including what is creativity, how to utilize local raw materials that can be processed into products, processing of natural materials into decorative products, processed food products from the forest product, packaging techniques and marketing of agricultural and forestry products, Medalsari village is quite famous as a village that has a natural attractions waterfall. Counselling activities for strengthening the creative economy based on village resources was followed by fifty participants could give benefit to the participants and expected to provide motivation to other communities. This could be seen from the enthusiasm of the participants in counselling and question-answering. It also appears that the participants feel motivated to develop their business creativity, as well as participants who only rely on their work as farmers, breeders and gardeners seem quite interested in trying to start developing their creative business.